Zasnova mobilne multimodalne komunikacijske naprave - osebni navigator - Kotnik, Bojan (Informacije MIDEM, 2001)
In today's world there are increasing demands for products that would enable a palette of services and would be portable, light, small and ergonomically designed. Their handling, however, should be as simple as possible, e.g. voice driven. Demands like that have brought about an integration of different technologies. The concept of the device which we describe in this article is called personal navigator. Personal navigator presents a multimodal communication device. It enables the user visual, tactile and voice communication. Visual and tactile communication between the user and the navigator runs over a graphical LCD display with touch-panel. Speech communication is supported by a powerfull digital signal processor, which makes automatic recognition and the synthesis of speech possible. That way, the personal navigator can be controled by speech. In that case ergonomically designed headphones are connected to the device, together with a combined microphone. The concept alone also includes image transmission, connection to the Internet and positioning - using Global Positioning System. Personal navigator also needs a navigation server, which runs on a PC. Combined GPS/GSM module/3/ is connected to the server. The GPS module in the navigation serveris needed for implementation of differential positioning; GSM module serves for establishing data connection with Personal navigator.
Keywords: GSM; kartiranje; mobilne komunikacije; multimodalne naprave; navigacijski strežniki; osebni navigatorji; podatkovne komunikacije; telecommunication; telekomunikacije